REVITALISASI DAN PEMBERDAYAAN FAKULTAS USHULUDDIN DAN DAKWAH: Kajian Atas Pengembangan Fak. Ushuluddin Dan Dakw IAIN Sultan Maulana Hasanuddin Banten - Hudaeri, Mohamad (UIN Ar-Raniry, 2014)
Faculty of Islamic Theology and Communication have an important position as a scientificcore or basic sciences in Islamic study that have a strategic role both in the development of Islamicknowledge or in character building. However, it is a reality, Theology is a faculty that hasfewer students than other faculties.But in fact, they had good quality. In this regard, the revitalization and empowermentat the faculty of Islamic Theology is an urgent matter. The article is focused on the search and analyze the existence of the Islamic Theologyand communication departmentof Islamic State of Sultan MaulanaHasanuddin, both in terms of its strengths and weaknesses, as well as the expectations and the challenges it faced. Therefore, thisÃ‚Â study includedinternal institutional and academic aspects and society'sÃ‚Â view toward the existenceof the Islamic Theology and Communication Department.